2021
DOI: 10.1111/myc.13362
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough invasive fungal infections in liver transplant recipients exposed to prophylaxis with echinocandins vs other antifungal agents: A systematic review and meta‐analysis

Abstract: Introduction:Although echinocandins are recommended as first-line prophylaxis for high-risk orthotopic liver transplant (OLT) recipients, occurrence of breakthroughinvasive fungal infections (IFIs) remains a serious concern. We aim to assess the risk of breakthrough IFIs among OLT recipients exposed to prophylaxis with echinocandins compared to other antifungals. Materials and methods: Two authors independently searched PubMed-MEDLINE, Embase, study registries and reference lists from inception to March 2021, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…Similarly, Wang et al, in a recent systematic review and meta-analysis of 69 randomized clinical trials that reported comparisons of 12 treatments with a total of 14,789 patients, concluded that voriconazole would be the best choice for patients undergoing HSCT, thus contrasting with some past studies that gave preference to posaconazole. 53 In any case, as posaconazole is not available in UHS, voriconazole (available for hospital use) is the viable option in Brazil's public health system. 20,28,[30][31][32][33]54 Micafungin may also be a beneficial option for prophylaxis of IFIs in HSCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wang et al, in a recent systematic review and meta-analysis of 69 randomized clinical trials that reported comparisons of 12 treatments with a total of 14,789 patients, concluded that voriconazole would be the best choice for patients undergoing HSCT, thus contrasting with some past studies that gave preference to posaconazole. 53 In any case, as posaconazole is not available in UHS, voriconazole (available for hospital use) is the viable option in Brazil's public health system. 20,28,[30][31][32][33]54 Micafungin may also be a beneficial option for prophylaxis of IFIs in HSCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Da mesma forma, Wang et al, em uma revisão sistemática e metanálise recente sobre 69 ensaios clínicos randomizados que relataram comparações de 12 tratamentos com um total de 14.789 pacientes, concluíram que o voriconazol seria a melhor opção para pacientes submetidos a TCTH, contrastando, dessa forma, com alguns estudos passados que davam preferência ao posaconazol. 53 De qualquer maneira, como não há disponibilidade do posaconazol no SUS, o voriconazol (disponível para uso hospitalar) é a opção viável no sistema público de saúde do Brasil. 20,28,[30][31][32][33]54 A micafungina também pode se apresentar como uma opção benéfica para profilaxia de IFIs em pacientes com TCTH, podendo ser usada em combinação com itraconazol ou fluconazol, e esse consenso não mudou na atualidade.…”
Section: Discussão E Conclusãounclassified
“…47 Echinocandins are associated with fewer toxicities and drug-drug interactions, but there are significant pharmacokinetic-pharmacodynamic limitations. Echinocandins achieve limited therapeutic concentrations intra-abdominally because of their molecular characteristics, 48 predisposing patients to the emergence of echinocandin resistance. 49 An 8% acquired resistance rate 50 and breakthrough invasive fungal infections 48 while on echinocandin therapy have been noted.…”
Section: Antifungal Prophylaxis In Liver and Lung Transplant Recipientsmentioning
confidence: 99%
“…Echinocandins achieve limited therapeutic concentrations intra-abdominally because of their molecular characteristics, 48 predisposing patients to the emergence of echinocandin resistance. 49 An 8% acquired resistance rate 50 and breakthrough invasive fungal infections 48 while on echinocandin therapy have been noted. To help prevent the emergence of fluconazole and echinocandin resistance, AMS programs can assist in optimizing dosing for patients who are critically ill, who require renal replacement therapy, or who have infections at sites of known poor drug penetration.…”
Section: Antifungal Prophylaxis In Liver and Lung Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation